Analisis Statistik Sederhana Untuk Pengambilan Keputusan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRAK A Table construction by a tally is data analysis which can easily be accomplished. At present, with an aid of computers, such analysis can be executed more with ease. Thus, anyone regarless of her or his academic backgrounds, should be able to make tables, graphs or descriptive statistics in a relatively short time. In constructing of such tables it is paramount that one should select appropriate variables (indicators or factors) so the tables may be utilized as inputs for decision makers, policy makers, and programs. An analysis based on these tables and graphs could be formulated as a descriptive summary. Keywords: decision makers, policy makers